171k views
2 votes
F(x)=-2x² + 3x-6, find f (3)

User Samazi
by
5.9k points

2 Answers

1 vote

Answer:

f(3) = -15

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

Brackets

Parenthesis

Exponents

Multiplication

Division

Addition

Subtraction

Left to Right

Algebra I

Functions

Function Notation

Step-by-step explanation:

Step 1: Define

f(x) = -2x² + 3x - 6

f(3) is x = 3 for the function f(x)

Step 2: Evaluate

Substitute in x [Function]: f(3) = -2(3)² + 3(3) - 6

Exponents: f(3) = -2(9) + 3(3) - 6

Multiply: f(3) = -18 + 9 - 6

Add: f(3) = -9 - 6

Subtract: f(3) = -15

User Sebcoe
by
5.1k points
5 votes

Answer:

f(3) = -15

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation

Explanation:

Step 1: Define

f(x) = -2x² + 3x - 6

f(3) is x = 3 for the function f(x)

Step 2: Evaluate

  1. Substitute in x [Function]: f(3) = -2(3)² + 3(3) - 6
  2. Exponents: f(3) = -2(9) + 3(3) - 6
  3. Multiply: f(3) = -18 + 9 - 6
  4. Add: f(3) = -9 - 6
  5. Subtract: f(3) = -15
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.